What is the value of health emergency preparedness exercises? A scoping review study. (March 2017) - Skryabina, Elena; Reedy, Gabriel; Amlôt, Richard; Jaye, Peter; Riley, Paul
Abstract: Emergency exercises involving the health community are considered an important and integral part of emergency preparedness activities. However, little is known about whether these exercises are effective at improving individual and/or organisational preparedness for responding to emergencies. This paper reviews and summarises published evidence on the effectiveness and benefits of exercises to prepare health emergency professionals for responding to emergencies and disasters. A literature search strategy was designed to identify the relevant publications from four major medical databases (Medline, Embase, Global Health and CINAHL). Studies meeting our inclusion criteria were analysed in detail (N=86). Both qualitative and quantitative data were reviewed. Data analysis involved a descriptive summary and a thematic analysis. Health emergency preparedness exercises were found to be effective (post exercise) at improving participants' knowledge of emergency activities, policies and procedures and improving overall competence and confidence. Other immediate individual benefits included improved perceptions of preparedness and improved understanding of individual roles and roles of partners. Whether these improvements persist over time and translate into improved emergency response is not clear. The most commonly reported post-exercise organisational benefits were: identifying gaps or limitations in plans, protocols or procedures and providing opportunities to share lessons. Only a few identified studies reported the long-term impact of exercises on job practices and on real emergency response. Published evidence of exercises impact on individual and organisational levels of emergency preparedness and response over the long term is very limited. The majority of the studies included (n=65, 76%) were US-based.